MICROSTRUCTURE AND ELEMENTAL COMPOSITION OF OBSIDIAN FROM THE ALMALO 1 LOCATION IN DAGESTAN: THE SOURCE OF THE RAW MATERIAL AND THE DIRECTION OF CULTURAL RELATIONS - Amirhanov, Hizri Amirhanovic; Cel'movic, Vladimir Anatol'evic (History, Archeology and Ethnography of the Caucasus, 2022)
The collection of archeological sites of the North Caucasus sometimes contain obsidian artefacts. The question of the sources of this type of raw material, with the use of possibilities of natural science methods for the region under study, has not been raised before. Meanwhile, for such a region as the North-Eastern Caucasus, where there are no natural outcrops of obsidian, the results of a comparative analysis of artifacts from this material will be especially clear in terms of establishing cultural contacts or migrations that took place in the past. This paper presents the results of an analysis of the elemental composition and microstructure of an obsidian piece from the Neolithic site Almalo 1 in Primorsky Dagestan and provides a comparative analysis of the data with the indicators of reference samples from an obsidian deposit in the central part of the North Caucasus. The examination, carried out using optical and scanning electron microscopes with an attachment for energy-dispersive analysis (EDA), led to the conclusion that the obsidian raw material used to make the obsidian plate from the Neolithic collection of the Almalo 1 site comes from the Zayukovo deposit in the Central Caucasus in modern Kabardino-Balkaria. This means that the direction of cultural ties of the population, which inhabited the north of the Caspian lowland of modern Dagestan in one of the segments of the Neolithic Age, was oriented towards the Central Caucasus and the Ciscaucasian steppes. The results obtained do not exclude the possibility of migrations that had a corresponding direction at the indicated time.
Keywords: obsidian; raw materials; microstructure; compound; analytical methods; Neolithic; Dagestan; Almalo 1